Beyond symmetric self-assembly and effective molarity: unlocking functional enzyme mimics with robust organic cages - Andrews, Keith G. (Beilstein Journal of Organic Chemistry, 2025)
The bespoke environments in enzyme active sites can selectively accelerate chemical reactions by as much as 1019. Macromolecular and supramolecular chemists have been inspired to understand and mimic these accelerations and selectivities for applications in catalysis for sustainable synthesis. Over the past 60+ years, mimicry strategies have evolved with changing interests, understanding, and synthetic advances but, ubiquitously, research has focused on use of a molecular “cavity”. The activities of different cavities vary with the subset of features available to a particular cavity type. Unsurprisingly, without synthetic access to mimics able to encompass more/all of the functional features of enzyme active sites, examples of cavity-catalyzed processes demonstrating enzyme-like rate accelerations remain rare. This perspective will briefly highlight some of the key advances in traditional cavity catalysis, by cavity type, in order to contextualize the recent development of robust organic cage catalysts, which can exploit stability, functionality, and reduced symmetry to enable promising catalytic modes.
Keywords: cavity confinement catalysis; enzyme mimicry; robust organic cages; self-assembly; supramolecular catalysis